Action Management of Commercial Sex Worker Cases - Kurniawan Gumalangit (Universitas Negeri Gorontalo, 2023)
This study aims to determine qualitative study of handling cases of commercial sex workers.The method used in this study is empirical legal research methodology and uses a qualitative approach to descriptive qualitative analysis techniques. The results of this study indicate thatLaw Enforcement in Handling Commercial Sex Workers (PSK) in Gorontalo City is carried out in two ways, namely preventive enforcement and repressive enforcement. Preventive enforcement of course there are various steps taken to prevent the practice of prostitution, namely legal counseling, conducting patrols and giving warnings. Meanwhile, repressive enforcement is carried out in two ways, namely coaching and inviting parents. So that from law enforcement it can be seen that there has been no implementation of the provisions of regional regulations that have been made such as the imposition of criminal sanctions, but only the imposition of social sanctions by the law enforcers themselves.